Watershed services payments to smallholders in the Brazilian Amazon: challenges and perspectives - Ricardo de O. Figueiredo (Ambiente & Água - An Interdisciplinary Journal of Applied Science, 2013)
Several hydrobiogeochemical research activities have been conducted in the EasternAmazon, contributing to the understanding of how changes in forests and agro-ecosystemsaffect the provision of services to ecosystems. The findings have demonstrated that goodagricultural practices and the presence of natural secondary vegetation favored by themanagement of small family farms are important factors for hydrobiogeochemical cycling,aquatic ecosystem conservation, soil conservation, and mitigation of trace gases emissionsfrom biomass burning in Amazonian small catchments. Two challenges for watershed servicemanagement arise in this context. First, low population densities and the relatively flatlandscape mean that a critical mass of downstream beneficiaries of such services - aprerequisite for public intervention is more difficult to identify than in more denselypopulated mountainous areas. Second, although watershed service providers (farmers) arealso to a considerable extent service beneficiaries, conflicts over land and culturalheterogeneities among settlers inhibit local collective action to safeguard the quality of streamwater. Including small landholders in carbon payment schemes that compensate for themaintenance of riverbank vegetation would appear to be a cost-effective means to securewatershed services as additional benefits of forest-based mitigation of climate change.